2019
DOI: 10.1002/cctc.201901604
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytically Active Silver Organic Framework: Ag(I)‐Complex Incorporated in Activated Carbon

Abstract: Silver is known as a viable alternative for platinum group metals for the catalysis of the oxygen reduction reaction in alkaline electrolyte. Unlike most other platinum-group metal-free catalysts, usually organo-metallic complexes, silver is commonly used in its metallic form (Ag(0)). Herein, we describe the preparation, characterization, and electrochemical activity of a unique silver-based catalyst, based on Ag(I) ions coordinated to oxygen groups in an organic ligand (benzene tricarboxylic acid -BTC) which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…As can be seen in the RDE results in Figure , the YbMOF-carbon composites have much higher electrocatalytic activity than the ligand and the AC without metal (BTC@AC). The carbon presents only a partial reduction of the oxygen to peroxide anion, instead of hydroxide, via the less desired two-electron reduction mechanism. ,, On the other hand, the YbBTC@AC (and YbBTC@BP2000 as well in Figure S5) demonstrates relatively high performance for a PGM-free ORR electrocatalyst, especially for a catalyst that did not undergo any thermal treatment, a process that has been proven in many cases to increase the electrocatalytic activity, with the onset and half-wave potentials of 0.88 and 0.75 V vs RHE, respectively. It can be speculated from the two different waves in the RDE voltammogram that the composite reduces oxygen via the 2 + 2 electrons mechanism, with the majority of the oxygen reduced to peroxide anion at the lower overpotential potential region, followed by the reduction to hydroxide at the higher overpotential (second wave).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen in the RDE results in Figure , the YbMOF-carbon composites have much higher electrocatalytic activity than the ligand and the AC without metal (BTC@AC). The carbon presents only a partial reduction of the oxygen to peroxide anion, instead of hydroxide, via the less desired two-electron reduction mechanism. ,, On the other hand, the YbBTC@AC (and YbBTC@BP2000 as well in Figure S5) demonstrates relatively high performance for a PGM-free ORR electrocatalyst, especially for a catalyst that did not undergo any thermal treatment, a process that has been proven in many cases to increase the electrocatalytic activity, with the onset and half-wave potentials of 0.88 and 0.75 V vs RHE, respectively. It can be speculated from the two different waves in the RDE voltammogram that the composite reduces oxygen via the 2 + 2 electrons mechanism, with the majority of the oxygen reduced to peroxide anion at the lower overpotential potential region, followed by the reduction to hydroxide at the higher overpotential (second wave).…”
Section: Resultsmentioning
confidence: 99%
“…Electrical Conductivity Measurements. Bulk conductivity of the electrocatalyst powder was measured using a twoprobe measurement method reported by Elbaz et al 18,35,36 Thirty milligrams of powder was placed in a 0.25″ diameter Teflon cylinder and compacted by two 0.25″ diameter alumina rods with tips covered in Au. The rods were two-bore in configuration, permitting Au wire to contact the Au foil.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 31 ] Gonen et al have reported a benzene tricarboxylic acid Ag(I) complex and studied its electrocatalytic activity toward oxygen reduction reaction (ORR). [ 32 ] Sherine et al have synthesized a 2‐Mercaptobenzothiazole (MBT) Ag(I) complex and the mechanism for its induction of apoptosis was confirmed by electrochemical analysis. [ 33 ]…”
Section: Introductionmentioning
confidence: 99%
“…[31] Gonen et al have reported a benzene tricarboxylic acid Ag(I) complex and studied its electrocatalytic activity toward oxygen reduction reaction (ORR). [32] Sherine et al have synthesized a 2-Mercaptobenzothiazole (MBT) Ag(I) complex and the mechanism for its induction of apoptosis was confirmed by electrochemical analysis. [33] In this work, we selected two different V-shaped bis (benzimidazole) ligands, 1,3-bis[(N-methyl-benzimidazole)methylene]-2-aniline (L 1 ) and 1,3-bis[(Nethyl-benzimidazole)methylene]-2-aniline (L 2 ), with isophthalic acid as auxiliary ligand, two new Ag(I) complexes, [Ag 2 L 1 2 (isophthalate)]Á(C 2 H 5 OH) 5 (1) and [Ag 2 L 2 2 (isophthalate)] (2), were synthesized and characterized by elemental analysis, IR and UV-vis spectra, and single crystal X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%